Gut Exteriorization in Emergency Laparotomies - Asifa Dian, Tasleem Akhtar, Rahat, Muhammad Hanif, Azam Yusuf (Journal of Rawalpindi Medical College, 2014)
Background: To evaluate the causes and management of emergency exteriorization. Methods: In this descriptive observational study ninety eight patients undergoing emergency laparotomy were included. In all these patients either gut exteriorization or primary anastomosis was done. On arrival in emergency initial resuscitation was performed. Usually Hollister or Convatec colostomy bags with wafers and Stoma adhesive paste was used and bags were applied.In loop colostomies and ileostomies, either perforation was exteriorised as such (posterior gut wall intact) or posterior wall repaired and then exteriorised at the same place. The afferent limb of loop ileostomy was everted to minimise local skin complications. Double barrel ileostomy was essentially an end ileostomy with mucous fistulae (two ends at same site) done. Ileocolostomy also had the same principle. Primary anastomosis was done with single layer extramucosal stitches. Results: Out of 98 emergency laparotomies for gut related pathology majority (74.49%) were males. The mean age of patients was 36 ±12.59 years with range of 07 – 75 years of age. Ileostomy was the most commonly performed (57.1%) procedure. Typhoid perforation (37.4%) and tuberculosis (28.91%) were the commonest indications . Conclusion: Infective disease is the most common indication for emergency gut exteriorization.